Impact of COVID-19 on the private and professional lives of highly educated women working in global health in Europe—A qualitative study - Hoffmann, Christina; Schneider, Tamara; Wannous, Chadia; Nyberger, Karolina; Haavardsson, Ingeborg; Gilmore, Brynne; Quigley, Paula; Winkler, Andrea S.; Ludwig, Sabine (Frontiers in Global Women's Health, 2023)
Background The COVID-19 pandemic has led to a deepening of already existing inequalities and to a roll back of achievements made in gender equality. Women in Global Health (WGH) is a global movement that aims to achieve gender equality in health and increasing female leadership in global health. Here the aim was to understand how the pandemic affects the private and professional life of women working in global health in different European countries. Suggestions for future pandemic preparedness including how gender perspectives should be integrated in pandemic preparedness, and how WGH helped to overcome the impact of the pandemic were explored. Methods Qualitative semi-structured interviews were conducted in September 2020 with a sample size of nine women from the different WGH European chapters. The participants were informed on the study and were formally asked for their consent. The interviews were held in English via an online videoconference platform and lasted 20-25 minutes each. The interviews were audio recorded and transcribed verbatim. Thematic analysis was conducted according to Mayring Qualitative Content Analysis using MAXQDA. Results The pandemic has both positive and negative effects on the professional and private life of women. It led to an increased workload and stress as well as pressure to publish on COVID-19 related themes. Increased childcare and household responsibilities represented a double burden. Space available for home office work was scarce if other family members were also working from home. Positive aspects included more time for family or partners and reduced travel. Gender differences in the experience of the pandemic were reported. International cooperation is considered to be a key factor for future pandemic preparedness. WGH was perceived as being very supportive in difficult situations during the pandemic. Conclusion This study provides unique insights into the experiences of women working in global health in different European countries. The COVID-19 pandemic influences their professional and private lives. Differences are seen between men and women. The need for gender perspectives in pandemic preparedness is therefore critical. Networks for women, such as WGH, can facilitate the exchange of information in crisis situations and provide women professional and personal support.